2016
DOI: 10.1177/0093854816657577
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Career Stage on Police Officer Work Behavior

Abstract: Career stage theory suggested that workers progress through career stages, each marked by unique work attitudes. Little evidence exists, however, about the influence career stages have on the work activities of criminal justice agents. Using a sample of 401 police officers from 23 individual police departments, the present study examined the influence of employee career stage on three measures of work productivity, and the constructs of expectancy motivation theory. The results revealed curvilinear declines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…The Present Study and the De-Policing Continuum Lafrance (2016: 1586) conducted research examining the issuance of citations for minor transgressions, impaired driving arrests, and illicit drug arrests, which they observe "result most often from proactive stops or investigations" rather than from dispatched calls. Similar to previous studies that found discretionary policing initiatives decline significant with experience (e.g., see Riksheim & Chermak 1993;Sherman 1980;Skogan & Frydl 2004), these policing scholars found that productivity, in all of the three areas measured, dropped precipitously among officers with ten or more years of (overall) police service (Johnson & Lafrance 2016). Their findings are consistent with the conceptual framework of a de-policing continuum as it is understood within the present study -in that, in a general sense, it can be expected that for many rank-and-file officers (among those that ultimately decide that their best interest is served by engaging in de-policing behaviours) their risk averse practices will change Gecas 2010), who found, "Unlike the findings on police burnout, de-policing does not appear to be present solely in veteran officers."…”
Section: The De-policing Continuumsupporting
confidence: 80%
See 2 more Smart Citations
“…The Present Study and the De-Policing Continuum Lafrance (2016: 1586) conducted research examining the issuance of citations for minor transgressions, impaired driving arrests, and illicit drug arrests, which they observe "result most often from proactive stops or investigations" rather than from dispatched calls. Similar to previous studies that found discretionary policing initiatives decline significant with experience (e.g., see Riksheim & Chermak 1993;Sherman 1980;Skogan & Frydl 2004), these policing scholars found that productivity, in all of the three areas measured, dropped precipitously among officers with ten or more years of (overall) police service (Johnson & Lafrance 2016). Their findings are consistent with the conceptual framework of a de-policing continuum as it is understood within the present study -in that, in a general sense, it can be expected that for many rank-and-file officers (among those that ultimately decide that their best interest is served by engaging in de-policing behaviours) their risk averse practices will change Gecas 2010), who found, "Unlike the findings on police burnout, de-policing does not appear to be present solely in veteran officers."…”
Section: The De-policing Continuumsupporting
confidence: 80%
“…Nevertheless, this is interesting to consider and may represent, among some officers especially close to retirement, the distancing from all aspects of the job -including perhaps de-policing practices, which was referred to by Labaky (2013) (1999) found that officers begin their policing careers motivated to perform proactive work in the field, however, Patrol officers became burned out from performing the same tasks for so long, and became disgruntled from experiencing injuries, lawsuits, citizen complaints, and being passed over for promotions or transfers. Finally, in the last career stage, Barker suggested that patrol officers began to disengage from the career, focusing more on outside interests and avoiding any risky situations that might jeopardize their retirement pensions (Johnson & Lafrance 2016: 1594.…”
Section: Career Stages and The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it could be argued that police culture in the given context might not be so powerful as to influence all police officers to develop the same attitudes at the same level. Further, similar to this argument some researchers also suggest that police attitudes might change with the years of service (Johnson and Lafrance, 2016; LaFrance and Day, 2013). The research shows that police officers’ attitudes toward standard operating procedures (LaFrance and Day, 2013) and the predicative values of opportunity, ability, and instrumentality on work activities vary with their career stage (Johnson and LaFrance, 2016) and follow a curvilinear pattern.…”
Section: Discussionmentioning
confidence: 54%
“…Further, similar to this argument some researchers also suggest that police attitudes might change with the years of service (Johnson and Lafrance, 2016; LaFrance and Day, 2013). The research shows that police officers’ attitudes toward standard operating procedures (LaFrance and Day, 2013) and the predicative values of opportunity, ability, and instrumentality on work activities vary with their career stage (Johnson and LaFrance, 2016) and follow a curvilinear pattern. These arguments invite us to use a longitudinal research design to examine such attitude changes or adaptation of police officers during their career stages.…”
Section: Discussionmentioning
confidence: 54%